Introduction of the low risk ankle rule to a paediatric emergency department. Issue 3 (March 2020) - Tormey, P.; Callender, O.; Fitzpatrick, P.; Okafor, I.; McNamara, R.; Kandamany, N.
Highlights: This paper provides further support for the use of the LRAR in children. It highlights significant financial savings that can be made with the LRAR. It provides further reassurance regarding risk of missing clinically significant injuries. This paper contributes to help reduce x-rays in children in line with the ALARA principle. Abstract: Introduction: Ankle injuries are a common presentation to the paediatric emergency department (PED), accounting for approximately 2% of presentations. 1 X-rays are ordered for 85–95% of patients but only 12% of x-rays reveal a fracture. Clinical prediction rules, such as The Low Risk Ankle Rule (LRAR) exist to help clinicians safely reduce the frequency of radiography in these injuries. The LRAR has been shown to reduce imaging by up to 60% without missing any clinically significant fractures. We sought to introduce The LRAR into our department and study its outcomes on our practice. Aims: To introduce the LRAR into our department and study its effects on our radiography rate and length of stay (LOS). Methods: An audit of x-ray rates in ankle injuries in 2016 was performed to determine our department's baseline rate of radiography and LOS. We then conducted education sessions and created x-ray ordering prompts to encourage clinicians to use the LRAR. We introduced the LRAR, with a pilot period initially, and gathered data prospectively. Results: 969 patients presented in with an ankle injury in 2016, 90.7% of these patients had an x-ray. The median LOS was 109 min. 92 patients presented during the LRAR implementation period with an ankle injury. Nine patients had exclusion criteria from using the LRAR and the attending physician did not use the LRAR in four patients. Of the remaining 79 patients, 49 had a LRAR positive exam. Only one of these patients went on to have an x-ray, which was normal. The 30 patients with a LRAR negative exam all had an x-ray. Overall, our x-ray rate during the study period was 40/92 (43.4%), a reduction of 47.3%. The average LOS during the study was 101 min. No clinically significant fractures were missed. Conclusion: The LRAR can safely and effectively reduce the rate of radiography in ankle injuries, without missing any clinically significant fractures.